2020
DOI: 10.21608/jacb.2020.108796
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yield, Fruit Quality and Molecular Diversity for Three Grape Cultivars under New Valley Conditions

Abstract: The current investigation was performed to evaluate the performance and DNA molecular analysis of three grape cultivars under the New Valley governorate, Egypt conditions. Most of the evaluated traits significantly varied among the cultivars. Superior cultivar had the best performance in cluster trait (weight, length and width), berries trait (number per cluster and 100 berries weight) and the total yield per vine. On the other hand, Flame cultivar overtopped in some quality traits (Total Soluble Solids, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…More importantly, SCoT marker is generated from the functional region of the genome, so genetic analyses such as genetic diversity, genotype identification, construction of linkage maps and QTL mapping using this marker would be more useful (Hajibarat et al, 2015). This result agrees with Gorji et al (2011) in Potato and Etminan et al (2016) in durum wheat, Abdel-Hameed et al (2020), andBashandy et al (2020) in grape. They found that the SCoT marker was more informative and effective than the ISSR marker to estimate the genetic diversity and perform fingerprinting in these plants.…”
Section: Molecular Assessmentsupporting
confidence: 69%
See 1 more Smart Citation
“…More importantly, SCoT marker is generated from the functional region of the genome, so genetic analyses such as genetic diversity, genotype identification, construction of linkage maps and QTL mapping using this marker would be more useful (Hajibarat et al, 2015). This result agrees with Gorji et al (2011) in Potato and Etminan et al (2016) in durum wheat, Abdel-Hameed et al (2020), andBashandy et al (2020) in grape. They found that the SCoT marker was more informative and effective than the ISSR marker to estimate the genetic diversity and perform fingerprinting in these plants.…”
Section: Molecular Assessmentsupporting
confidence: 69%
“…Previous studies were focused on describing and evaluating grape cultivars (Brooks and Olmo 1972;Watt, 1983;Walker and Boursiquote, 1992;Abd El-Kawi and El-Yam, 1992 a, b and c;Abd El-Fattah and Kastor, 1993 a and b;Morrison, 1994;Tourky et al, 1995;El-Sharkawy 1995;Fawzy 1998;Marwad, 2002 a and b;Gaser, 2006;Girgis 2007;Sabry et al, 2009;Abd El-Rahman, 2016;Tarbia, 2017 andEl-Morsy et al, 2017). Recently, some studies have used SCoT and ISSR markers successfully together successfully in the molecular diversity assessment of grape varieties, such as Abdel-Hameed et al (2020) and Bashandy et al (2020). Whereas they explain that both methods were effectively efficient for studying the genetic diversity in grape until between closely related cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees with Abdel-Hameed et al (2020); Bashandy et al (2020); Ola-Ahmed and Abd EL-Aziz (2021) in Grape, Gorji et al (2011) in potato and Etminan et al (2016) in durum wheat. They found that the SCoT marker was more informative and effective than the ISSR marker to estimate the genetic diversity and perform fingerprinting in these plants.…”
Section: Resulted Data Comparison Of Discriminating Capacity Between ...supporting
confidence: 91%
“…The honeydew of mealybugs can also encourage the development of bacteria or fungus, such as black sooty mold which prevents sunlight from penetrating the leaves and cane inhibit plant growth. Bashandy et al (2020) found that, there were significant differences between the studded cultivars in physical quality parameters. The interaction between grape varieties and different insecticides showed the significant differences in second season.…”
Section: -Yield and Fruit Quality: 2-1: Yield /Vine (Kg)mentioning
confidence: 90%